Poetry Creation Training Towards FLS2N 2025 For Teachers of Indonesian Language Mgmp in Kampar District: Efforts to Improve Teachers' Literacy Competence - Piliang, Wilda Srihastuty Handayani; Roziah, Roziah; Wulandari, Fitri (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
Poetry training for MGMP Indonesian Language teachers in Kampar District is a strategic effort to improve literacy competence in writing and guiding students for the 2025 National Student Art Festival and Competition (FLS2N). This activity was implemented through an integrated approach that combines theory, hands-on practice, and technology-based mentoring, involving competent poets in the field. The results of the training showed significant improvements in the understanding of poetry structure and aesthetics, writing skills, as well as teachers' motivation to develop literacy communities in schools. The resulting poems, highlighting local wisdom with mature writing techniques, met the criteria for creativity and relevance to the FLS2N theme. In addition, the anthology of poems by teachers has the potential to become innovative teaching materials for literature learning in the classroom. This training not only has an impact on improving teacher competence, but also opens up opportunities for developing local culture-based poetry writing learning models.